The genome sequence of the Hebrew Character, Orthosia gothica (Linnaeus, 1758) - Boyes, D; Holland, PWH (F1000 Research Ltd, 2024)
We present a genome assembly from an individual female Orthosia gothica (the Hebrew character; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 1,065.1 megabases in span. Most of the assembly is scaffolded into 37 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.38 kilobases in length. Gene annotation of this assembly on Ensembl identified 13,691 protein coding genes.